Nipple–areola complex reconstruction improves psychosocial and sexual well-being in women treated for breast cancer. Issue 2 (February 2017) - Bykowski, Michael R.; Emelife, Patrick I.; Emelife, Nancy N.; Chen, Wendy; Panetta, Nicholas J.; de la Cruz, Carolyn
Summary: Introduction: Women choose to undergo nipple–areola complex (NAC) reconstruction as part of breast reconstruction following breast cancer treatment. However, the effect of this procedure on psychosocial and sexual well-being is not well studied. The present study aimed to evaluate how NAC reconstruction affects patient satisfaction with regard to psychosocial and sexual well-being. Methods: A retrospective chart review was performed for all patients who underwent NAC reconstruction at Magee-Women's Hospital from January 1, 2004 to July 31, 2011. A letter and questionnaire based on the BREAST-Q were mailed to patients to request their participation in the study. Patient satisfaction and health-related quality of life were measured before and after NAC reconstruction. Results: In total, 107 of 328 patients (32.6%) completed the survey. The BREAST-Q scale score for satisfaction with outcome following NAC reconstruction was 85.1 ± 15.8, with higher satisfaction scores for patients with a follow-up of <1.5 years than those with a follow-up of >2.5 years (82.5 ± 21.7 vs. 69.5 ± 19.5; p < 0.01). No significant differences were found in satisfaction with the breast mound before and after NAC reconstruction. Women scored significantly higher on the psychosocial and sexual well-being scales after NAC reconstruction ( p < 0.002 and 0.00004, respectively). Conclusions: This study indicates that patients are highly satisfied after undergoing NAC reconstruction. Satisfaction with the procedure, however, may decrease over time. NAC reconstruction significantly contributes to patient psychosocial and sexual well-being, and this effect did not change over time. NAC reconstruction improves patient outcomes in those who choose to undergo the procedure.